2016
DOI: 10.1515/tjb-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different eight-week walking programs on insulin resistance and ER stressrelated markers in pre-menopausal women / Premenopozal kadınlarda 8 haftalık farklı şiddetteki yürüyüş antrenmanlarının insülin direnci ve ER stresiyle ilişkili markerler üzerine etkileri

Abstract: Objective: The relationship between exercise and endoplasmic reticulum (ER) stress, insulin resistance, and obesity is a new field of research. To our knowledge, there are no studies examining the effects of walking exercises on ER stress related markers and insulin resistance in pre-menopausal women. To examine the effect of two different eight-week walking programs on the tumor necrosis factor-alpha (TNF-α), Fetuin-A (α2 - Heremans Schmid glycoprotein), c-Jun N-terminal kinase-1 (JNK-1) and retinol- binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In another study observed positive effects of walking exercises on body composition (Doğru, Büyükyazı, Ulman, Taneli, Tıkız, Göral, & Esen, 2016). It is possible to state that the exercise program we applied in our study had positive effect on strength.…”
Section: Discussionmentioning
confidence: 50%
“…In another study observed positive effects of walking exercises on body composition (Doğru, Büyükyazı, Ulman, Taneli, Tıkız, Göral, & Esen, 2016). It is possible to state that the exercise program we applied in our study had positive effect on strength.…”
Section: Discussionmentioning
confidence: 50%